ЭЛЕКТРОХИМИЧЕСКОЕ ИССЛЕДОВАНИЕ ПРОЦЕССОВ КОРРОЗИИ СТАЛЕЙ В МОРСКОЙ СРЕДЕ ТРОПИКОВ - Н.Г., Ануфриев; В.А., Карпов; Ю.Л., Ковальчук; Донг, Ван Киен; Н.Л., Филичев; Ми , Ле Тхиеп (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INVESTIGATION OF ELECTROCHEMICAL CORROSION OF STEEL IN TROPICAL MARINE ENVIRONMENTAn automatic electrochemical equipment has been developed to determine the corrosion rate of mild and stainless in tropical marine environment using methods such as linear polarization, zero-resistance and potentiometer. Long term performance and tropical stability of the equipment have been tested in laboratory conditions and the spray zone at sea stand in the Nha Trang bay. Testing results showed that the developed technique and equipment to determine electrochemical corrosion rat of 30KhGSA, 08kp, St3, 08Kh13 and NS-5T steels in tropical seawater provide adequate results in comparison with gravimeter methods.